Tocando (com) o lugar: os elementos meteorológicos como forças criadoras no processo de composição sonora e musical - Gomes, Henrique (2018)
The use of different methods of sonification of meteorological and geophysical data is recurrent both in scientific applications and in the context of artistic creation. It is proposed, through different approaches throughout the research process, the creation of a series of synthesizers and sound devices sensitive to variations of wind intensity, luminosity and ambient temperature. In order to explore the potentialities of using sonification of forces of nature as a method of sound and musical composition, several sensors are used to control different parameters of the digital sound synthesis process. Through the experimentation of circuits and programming codes in Arduino, it is sought to analyze the factors that influence different aspects of the composition process with the meteorological elements. The process of development of three synthesizers that are used in different occasions is presented, along with the construction of a sonifying machine and the production of diverse material about the process of elaboration of the prototypes. Based on the experiments carried out, aspects pertinent to the performance of elements of nature as creative forces during the process of sound and musical composition are identified.